Assessment of maternal-offspring selenium transfer in ewes and newborn lambs via serum, whole blood, and wool matrices - Caliskan, Mehmet (Elsevier, 2025)
Selenium (Se) is an essential micronutrient required by almost all organisms. Disorders associated with Se deficiency can occur in various animal species, but they are more common in ruminants, especially small ruminants. This study had two main objectives: first, to investigate whether there is a correlation between whole blood, serum, and wool Se levels in sheep and lambs individually; and second, to examine the relationship between Se levels in these matrices between ewes and their newborn lambs. Wool samples were collected from the sulcus jugularis region using a razor blade, and blood samples were obtained via jugular venipuncture from 18 ewes and their 18 colostrum-fed lambs aged 12 to 72 h. Significant correlations were found between serum and whole blood Se levels within both ewes (r = 0.72, p < 0.01) and lambs (r = 0.69, p < 0.01), indicating internal consistency within each group. Se concentrations in whole blood, serum, and wool samples were similar between ewes and lambs, with no statistically significant differences observed in any matrix (p > 0.05). While Se concentrations in whole blood showed a significant correlation between ewes and lambs (r = 0.65, p < 0.01), no such correlation was observed in serum or wool samples. These findings suggest that both whole blood and serum are suitable for assessing individual Se status in sheep and lambs, whereas whole blood may serve as a more reliable matrix for evaluating maternal-offspring Se transfer.
Keywords: Selenium status; Ewe-lamb correlation; Whole blood; Serum; Wool